Construção e validação de um instrumento de coleta de dados sobre competências em promoção de saúde - Wojcik, Leonice Ines (2013)
The aim of the study was to construct and validate an instrument to collect data on competences in health promotion and to test the instrument with graduates of Master on Health Promotion. The study was divided into five phases: preparation instrument, instrument validation, adequacy of the instrument, pilot study and application of the instrument to the subjects using a semi structured self-administered questionnaire, based on the European handbook "The CompHP Core Competencies Framework for Health Promotion Handbook". The application asked the 4th and 5th stages was conducted via online through Survey Monkey software. As a result, four judges evaluated the instrument as the evaluation criteria: objectivity, simplicity, clarity, relevance, accuracy, language, credibility, breadth and balance. We choose to modify the instrument prior to application of the pilot test. The result showed that the instrument was easy to apply, in general the questions were brought satisfactory performance and accurate answers. As regards the application of the instrument to a sample of Masters on Health Promotion, the responses focused on two items, " had already honed" and "non-owned and developed" core competencies in Health Promotion. It was possible to observe a positive transformation and constructive participants added and identified the key competences necessary for Promoting Health Equity, a competency was suggested. As conclusive evidence, the process of instrument validation demanded dedication, pilot testing allowed us to evaluate the changes and gave credibility to the developed instrument. The application brought to the public data on the change in their skills. Knowledge of skills are the result of accumulation of information, performance, personal skills, interests and needs of the individual. The construction of an instrument to assess the skills developed is a technique that can be used to deal with a complex evolution. Keywords: competence, health promotion, validation studies.